Dickson charge pump using integrated inductors in complementary metal–oxide semiconductor technology. Issue 3 (1st March 2016) - Zucchelli, Massimiliano; Colalongo, Luigi; Richelli, Anna; Kovacs‐Vajna, Zsolt M.
Abstract : A fully integrated DC/DC converter for low‐voltage applications is presented. It is based on a modified Dickson charge pump which exhibits improved performances by using integrated small inductors. The proposed charge pump is superior in terms of power efficiency, maximum output voltage, rise time, and voltage output ripple. The overall circuit does not require any external components and can be fully integrated in a standard complementary metal–oxide semiconductor technology. The converter has been designed in STMicroelectronics 180 nm process.